Quantifying Vulnerability to Poverty in the Drought-Prone Lowlands of Ethiopia - Skoufias, Emmanuel (World Bank, Washington, DC, 2021)
A forward-looking measure of “vulnerability to poverty” is estimated and a concerted effort is made to understand the sources of vulnerability in the drought-prone lowlands of Ethiopia. Using the Household Consumption Expenditure Survey and the Welfare Monitoring Survey of 2016, the analysis reveals that vulnerability is remarkably higher in the drought-prone lowlands than in the other ecological zones, although differences in poverty rates are modest; the vulnerability rate is more than two times larger than the poverty rate in the lowlands, while the ratio is only 1.6 for the whole country. The analysis also reveals important distinctions in the sources of vulnerability. In the drought-prone lowlands: (i) vulnerability due to aggregate shocks such as droughts is lower than vulnerability due to idiosyncratic shocks in absolute terms, but its relative importance is higher compared with other ecological zones; and (ii) poverty-induced vulnerability is relatively more important than risk-induced vulnerability in contrast to other regions where risk-induced vulnerability is higher than poverty-induced vulnerability. These findings attest to the unique nature of the drought-prone lowlands compared with the other agroecological zones and points in favor of policies and programs tailored specifically to the areas.